Marginalidade e angústia do sujeito contemporâneo: o projeto literário de Ferréz - Ricardo José dos Santos Neto (2021)
The hegemonic section of literature, across the years, created a literary ―tradition‖ based on specific ―tastes‖ pointed as aesthetically superior. The literary writing that didn't fit in the stands dictated by the ―taste‖ and ―tradition‖ was placed on the margins. In Brazil where hegemonic tradition strongly influences literary studies, many of the texts that disagree with the ―taste‖ were (and are) placed on the margins, and classified by the literary criticism under the title of marginal literature. Since the later '90s these publications started to gain force due to the desire of marginalized people to express themselves. Mostly, the marginal production has been emerged from peripheries and slums. One of the exponents of this literature is Ferréz who starts to receive notoriety from the release of his first novel, Capão Pecado. This work is marked by a narrative that shows the raw elements of the reality of the inhabitants of Capão Redondo, one of the most violent neighborhoods in Brazil. From the inaugural novel of Ferréz, a new literary modality is born, which is mainly articulated by the writer, also affirmed by the marginal literature collections organized for him. In these collections are published manifests that affirms the idea that marginalized people are able to speak by themselves, and for that, they use their own language as a power element. To these elements links the marginal writer engagement, who values the marginalized cultures and marginalized communities through socio-political actions. In addition to the analysis of the factors described, this dissertation studies briefly the most part of Ferréz works to make possible the comprehension of his litterary style. Deus foi almoçar is the author work deeper analyzed here. This analysis is justified because in this romance Ferréz walks in a different territory: the anguished subject lost in his/her own existential complexity, considering the periphery and the slum not as the center of the actions. Even having this variation added to the narrative form of the psychological novel and stream of consciousness, Deus foi almoçar brings the marginality project present in the other writer's works. In the novel we can see in the most blunt way, the severe author criticism to the consumer society and its way of life.